2021
DOI: 10.1038/s41541-020-00279-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of a SARS-CoV-2 DNA vaccine in wild-type and immunosuppressed Syrian hamsters

Abstract: A worldwide effort to counter the COVID-19 pandemic has resulted in hundreds of candidate vaccines moving through various stages of research and development, including several vaccines in phase 1, 2 and 3 clinical trials. A relatively small number of these vaccines have been evaluated in SARS-CoV-2 disease models, and fewer in a severe disease model. Here, a SARS-CoV-2 DNA targeting the spike protein and delivered by jet injection, nCoV-S(JET), elicited neutralizing antibodies in hamsters and was protective in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 20 publications
4
47
1
Order By: Relevance
“…Similar to our study, this vaccination did not affect viral shedding in pharyngeal swabs but did reduce weight loss over the course of infection. In contrast to our study, the nCoV-S(JET) did induce neutralizing antibodies and decreased areas of consolidation and SARS-CoV-2 RNA labeling in areas of inflammation in the lung [ 36 ]. The distinct outcomes in our study with those of nCoV-S(JET) study suggest that neutralizing antibodies may play an important role in diminishing COVID-19 disease progression.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Similar to our study, this vaccination did not affect viral shedding in pharyngeal swabs but did reduce weight loss over the course of infection. In contrast to our study, the nCoV-S(JET) did induce neutralizing antibodies and decreased areas of consolidation and SARS-CoV-2 RNA labeling in areas of inflammation in the lung [ 36 ]. The distinct outcomes in our study with those of nCoV-S(JET) study suggest that neutralizing antibodies may play an important role in diminishing COVID-19 disease progression.…”
Section: Discussioncontrasting
confidence: 95%
“…Our study and others evaluating DNA-vaccines [ 36 ] supports the need for boosting to achieve significant antibody titer increase [ 27 , 36 ], an important public health consideration for deployment of vaccines against SARS-CoV-2 [ 27 ]. Alternative vaccine platforms may provide significant protection against COVID-19 after just a single vaccination.…”
Section: Discussionsupporting
confidence: 71%
“…The hACE2 transgenic hamsters used here also provide a new and relevant model of severe/fatal SARS CoV-2 disease that can be utilized to test vaccines and therapeutics 25 . Consistent with other studies of hamsters, other experimental animals and potentially humans [29][30][31][32] , protection from severe disease was not closely associated with an effect on oropharyngeal swab titers; however, if control and SAb-185 treated animals that had delayed virus replication were removed, suppression of titers by SAb 185 was significant for combined challenge groups (p=0.02) on D5 post challenge. This contributes to the body of evidence that vaccination and/or Ab therapeutic treatment may only provide limited protection from virus infection and upper respiratory tract replication.…”
Section: Discussionsupporting
confidence: 87%
“…Macaques, especially Macaca mulatta appears to be the most susceptible to SARS-CoV-2; they developed COVID-19-like lung lesions albeit with moderate symptoms [32]. Presently, aged Rhesus macaques [33,34], baboons [35], hamsters [30,36] and mice [7À9,14] developed more severe disease (versus young) ranging from weight loss, exacerbated pneumonia, cellular pulmonary infiltration and Favipiravir, HCQ/azithromycin [52] Neutralizing mAb [55, 174, 191À195] Ranitidine bismuth citrate [196] Vaccine [62,165,197] Tree shrew [23,24] Low-to-high, Age-dependent susceptibility similar [49] Neutralizing mAb [17,192] Convalescent plasma & Remdesivir [16,37,54] Baicalein [198] Dalbavancin [162] interferon-λ1a [9] Vaccine [8,9,64,165,199] Plitidepsin [50] Cat [25,26] High cytokine release to respiratory dysfunction. Notably, one mouse study reported hyposmia/anosmia after intranasal SARS-CoV-2 inoculation [37].…”
Section: General Symptoms and Age Effectmentioning
confidence: 99%